The contemporary desire for a technified salvation - Montoya Camacho, Jorge Martín; Giménez Amaya, José Manuel (Razón y fe, 2023)
One of the main characteristics of the world we live in is what we call the presence of a metabolic vitalism. In this article, we want to delve into the anthropological-cultural use of this concept by relating it to human desires for happiness and salvation and the implications of technology in order to, finally, draw a conclusion through a possible dystopian scenario. We argue that the cultural supremacy of this type of vitalism has led to the obscuring of a natural and unitary vision of the experience of the expiration of the human body and, therefore of man’s natural need to be saved. From an anthropological point of view, we analyze that at the basis of this whole process is the curtailment of the natural ends of what we define as corporeal intentionality, which is difficult to understand if there is not an adequate integration, in a teleological way, of the biological and spiritual aspects of the human being.
Keywords: body; happiness; salvation; spirit; technology; teleology